Deteksi Dini Tumbuh Kembang Siswa Paud Laboratorium School Universitas Nusantara PGRI Kediri - Aizah, Siti; Mudzakkir, M.; Wijayanti, Endah Tri; Fitriana, Siti; Faruq, Najib Zahir Al; Ayu K, Ratih; Mahrufi, M. Amar; Aini, Pipit Nur; Kurniawati, Elsa Della (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Child growth and development is a complex process and takes place as long as the child is in the period of growth and development. Every child has a different speed of growth and development depending on genetic and environmental factors. Early detection through DDTK is very necessary to find early children who experience growth and development deviations so that intervention can be carried out as early as possible, so that the growth and development deviations experienced do not become permanent disabilities. DDTK activities are not only carried out on children who are suspected of having problems, but must be carried out routinely on all toddlers and preschool children so that the child's growth and development is optimal. Based on this, DDTK needs to be carried out on preschool students. The results of the DDTK carried out on PAUD Laboratory School students at Nusantara PGRI Kediri University were found to be mostly normal, namely examination of body weight, height and head circumference. Likewise, the development assessment found that the majority of children had development that was appropriate to the child's age or normal. Many factors influence a child's growth and development. Not only genetics inherited from parents, external factors such as nutritional intake also play an equally important role. To obtain optimal growth and development status, it is necessary to pay attention to the factors that influence flowering plants, especially for parents.